Design and Simulation of High Voltage Short Pulse Generator - et. al., G. Nithya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
High voltage pulse generators are widely applied in a many engineering fields. The aim of this paper is presenting a Design and Simulation of a high voltage short pulse generator using boost converter topology which is able to generate up to 5 kV for a varying resistive load of 5 to 20 Ω loads with a pulse width ranging from 1 to 10 μs. The switching frequency of the circuit is 30 kHz. Proposed converter is tested with different duty cycle and Resistance load (RL) with a constant input voltage multilevel DC-DC Boost converter in only on Continuous Conduction Mode (CCM). The performance parameters of the DC to DC boost converter are analyzed. This paper briefly investigates the technology used in high voltage DC to DC conversion in short pulse generator for energy transfer and also to convert low voltage into high voltage from input side to output side. Here the Simulation workouts are carried out by the MATLAB/SIMULINK 2019 a version to validate the proposed system results